Laser Drilling of Small Holes in Different Kinds of Concrete - Nagai, Kaori; Beckemper, Stefan; Poprawe, Reinhart (Civil Engineering Journal, 2018)
Recently, in Japan, safety measures such as earthquake-resistant reinforcement work and tile-reinforcement work are increasing. Current concrete drilling methods have issues such as noise, vibration, dust, and reaction force. These methods are causing stress for the residents. Consequently, solutions are being sought for work taking place on skyscrapers and at facilities that cannot shut down during construction, such as hotels, schools, hospitals and geriatric facilities for instance.Â  Â This study investigated how laser drilling change the conditions, depending on the type of concrete in order to determine the possibility of using laser drilling for tile-reinforcement work and repairing concrete on building exterior. The results confirmed that itâs possible to successfully drill holes for drilling diameters of 4 to 6 mm and depths of around 50 mm in concrete with a compressive strength within the range of 20 to 100 N/mm2 by adjusting laser conditions. In case of deep holes the CW-mode should be chosen. Furthermore, by controlling laser irradiation conditions, it is possible to change the shape of the holes. These different kinds of holes are suitable for different applications. It is expected that laser irradiation drilling will be applied to new construction methods.